2018
DOI: 10.18203/2394-6040.ijcmph20183609
|View full text |Cite
|
Sign up to set email alerts
|

Violence against health care workers: a provider’s (staff nurse) perspective

Abstract: Background: Work place violence has become an endemic problem for health care workers (HCW) worldwide. The staff nurses are the most vulnerable and most assaulted among all the health care workers. The study was conducted with an aim to assess the frequency of violence and factors responsible, the response of the staff nurses after an incident of violence, any association between the socio-demographic factors with the violence against the HCW and to seek the suggestions to stop/prevent such incidents.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 32 publications
5
27
0
2
Order By: Relevance
“…In studies conducted by Dixit et al, 61 Gohil et al, 39 and Mishra et al, 55 the participants reported that no action was taken following the incidents of WPV.…”
Section: Perpetrators Of Wpv and Measures Following Wpvmentioning
confidence: 99%
See 4 more Smart Citations
“…In studies conducted by Dixit et al, 61 Gohil et al, 39 and Mishra et al, 55 the participants reported that no action was taken following the incidents of WPV.…”
Section: Perpetrators Of Wpv and Measures Following Wpvmentioning
confidence: 99%
“…60 The quality evaluation using the NHLBI tool found no studies with poor quality, three studies with fair quality, 39,51,57 and remaining studies (n = 12) with good quality. 40,41,61,62,[52][53][54][55][56][58][59][60] Most of the studies (n = 14) recruited study participants from medical institutions in urban areas whereas only one study by Pund et al recruited from multiple locations in a district where 65.85% participants were working in rural areas. 57 All these studies were cross-sectional in nature and conducted using self-administered pre-tested questionnaires with different demographic and violence-related variables.…”
Section: Characteristics Of the Recruited Studiesmentioning
confidence: 99%
See 3 more Smart Citations